2021
DOI: 10.3390/agronomy11061196
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping Alfalfa into Silage Maize Can Be More Profitable Than Maize Silage Followed by Spring-Seeded Alfalfa

Abstract: Intercropping of silage maize (Zea mays L.) and alfalfa (Medicago sativa L.) is not a common practice because alfalfa generally reduces maize grain and biomass yield. The objective of this research was to evaluate the productivity and profitability of silage maize–alfalfa intercropping, with a goal to establish alfalfa and increase alfalfa productivity in the first year of production. The experiment was conducted in Fargo and Prosper, ND, USA, in 2014–2017. The design was a randomized complete block with four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 30 publications
2
26
2
Order By: Relevance
“…Conversely to our results, Grabber [13] and Berti et al [15] did not observe a significant reduction in silage corn biomass yield treatments where it was intercropped with alfalfa in normal rainfall conditions. It is possible that in average-rainfall situations, the environment within the canopy of silage corn does not favor alfalfa growth and thus decreases competition with corn early in the season.…”
Section: Corn Grain and Biomass Yield And Plant Heightcontrasting
confidence: 99%
See 4 more Smart Citations
“…Conversely to our results, Grabber [13] and Berti et al [15] did not observe a significant reduction in silage corn biomass yield treatments where it was intercropped with alfalfa in normal rainfall conditions. It is possible that in average-rainfall situations, the environment within the canopy of silage corn does not favor alfalfa growth and thus decreases competition with corn early in the season.…”
Section: Corn Grain and Biomass Yield And Plant Heightcontrasting
confidence: 99%
“…In summary, establishing alfalfa in intercropping with corn for grain is feasible and has multiple benefits to soil health and the environment in comparison with corn monoculture, as demonstrated by several pieces of research [14,15,19,30,32,37,48]. It has been demonstrated that alfalfa-silage corn intercropping systems have a higher total net revenue than corn monocultures, despite the yield penalty to corn in the seeding year [14,15,30]. All these studies have been conducted in silage corn and not corn for grain.…”
Section: Alfalfa Forage Nutritive Valuementioning
confidence: 99%
See 3 more Smart Citations